Effect of prebiotic (GroBiotic®-A) on the growth performance and intestinal microflora on rainbow trout (Oncorhynchus mykiss Walbaum) - Abdolhamid Azari; R, Hashim; G, Azari Takam; SMV, Farabi; M, Darvish; R, Safari (Journal of Research in Biology, 2011)
The use of prebiotics as feed supplements that improve efficiency of intestinal bacteria is becoming de rigueur in animal husbandry in many regions worldwide. We tested the effects of a commercial prebiotic (GroBiotic®-A) including yeast and dairy fractions in different levels on survival, growth, carcass composition and intestinal microflora on rainbow trout (Oncorhynchus mykiss Walbaum). In the present study, we were able to detect high amounts of lactic acid bacteria (LAB) in the intestine after 12 weeks of prebiotic supplementation, conducted. Ultimately, when all supplementation diets are considered, GroBiotic®-A inclusion to diets for appearing on increase on growth, survival, and carcass composition on O. mykiss